Impact of Price, Product and Collaboration on Market Value: Strategic Responses Against Open Source Software - Yang, Kuoh Siong (2005)
Open source software, commonly regarded as a disruptive technology, is gaining a foothold in mainstream software applications. Developers of proprietary or closed source software are aware of this threat and responding through various strategies. In this paper, we discuss the genesis of open source software and motivation for its continued diffusion as well as propose attributes that qualifies it as a disruptive technology. We examine the types of responses that are available in the face of disruptive innovation and offer reasons for established companies taking their course of actions. We segregate responses from closed source developers based on intent and investigate the impact of price cuts, product launches and collaboration on their market values using event studies methodology. Our result shows that when the intent is to protect its market share against open source software, the market responds positively to announcements on price cuts whereas when the intent is to create a new market or expand an existing market, announcements on new product launches and collaborative efforts will result in abnormal returns for the closed source software companies.